Dengue shock syndrome: An evaluation of clinical experiences - Muzief Munir; T. H. Rampengan (Paediatrica Indonesiana, 1984)
Experiences on the clinical management of 187 criteria accepted cases of Dengue Shock Syndrome were evaluated. The case fatality rate was 8 per cent or 15 out of 187 cases. It was closely related to the severity of shock, the respiratory rate, the body temperature during shock, and the development of recurrent shock. It was also found that the risk to develop recurrent shock was higher among cases with severe shock, high respiratory rate, and high fever.